Reconfiguring Archilochus. How have papyri and inscriptions changed perceptions of Archilochus’ iambic and elegiac poetry? - Bowie, Ewen L. (Ariadne, 2020)
THIS paper explores the ways in which the publication of new texts preserved on papyri and inscriptions substantially changed our understanding of what a book of Archilochus’ iambic or elegiac poetry would have been like. The papyri (of which the first was published in 1891, but the majority in the 1920s and 1950s) showed that Archilochus’ iamboi had at least as much narrative as invective—narrative relating to polis concerns like war (also attested in epigraphic snippets) and to the private, and especially sexual, life of the persona loquens. This last was most strikingly shown by the Cologne epodes published in 1974. The elegiac corpus, whose few quoted poems or fragments were chiefly sympotic and encouraged a view of Archilochus’ poetic persona as antiheroic, benefited less than iambi from papyrus finds until in 2005 the Oxyrhychus ‘Telephus’ was published. Its 25 lines narrating Telephus’ rout of the Achaeans who disembarked in Mysia, mistaking it for Troy, corroborated the underexploited indications of Longinus and Dio that Archilochus used elegiacs for mythical narrative.